The Influence of Coffee Shop Atmosphere on Student Decision-Making in Choosing a Place to Study at Tanama Coffee Shop UMKM in Pekanbaru City: (Case Study of Students of Riau Islamic University) - Mohd. Handria Pratama; Syahdanur (Majapahit Journal of Islamic Finance and Management, 2026)
The purpose of this study was to analyze and determine the significant influence of coffee shop atmosphere on students' decision-making in choosing a learning place at the Tanama Coffee Shop SME in Pekanbaru City. This study was conducted on students at the Islamic University of Riau. The sample size consisted of 100 active and registered students at the Islamic University of Riau. This sample was obtained through purposive sampling and statistical calculations using the Lemeshow formula. The data analysis method used in this study was quantitative statistical analysis with a simple linear regression model. Based on the results of the research data analysis, it can be concluded that the coffee shop atmosphere has a positive (+) and significant influence on the decision of students at the Islamic University of Riau regarding the restoration of the learning space at Tanama Coffee & Space in Pekanbaru City